Nation-building among youths in Malaysia: The civic education approach - Nor Hafizah, Abdullah; Mohd Mahadee, Ismail; Zaini, Othman (2019)
This article focuses on the nation-building among youths in Malaysia through civic education. Today's youths are exposed to various social challenges, including domestic and global intimidations, and they are easily involved in social problems and immoral activities. Moreover, some of the youths are seen as close-minded, lack respect for the elders and intolerant in their daily life which may affect inter-ethnic relations in a multiethnic society. It is crucial to foster the youths to ensure a better development of the country. The government has implemented civic education approach in educating the youths to foster a strong patriotism and nationalism, and strengthen their loyalty towards the country. The purpose of this study is to provide insights into the implementation of civic education approach cultivating civic consciousness among the Malaysian youth groups. This study employed quantitative approach through a survey technique by using questionnaires distributed to 431 Malaysian youths from Universiti Putra Malaysia (i.e 241 Malay and 190 Chinese students). Descriptive analysis was implemented to compare and contrast the intensity of civic education based on three dimensions, namely civic knowledge, civic skills and civic disposition. The findings show that the Malay and Chinese respondents have high levels of civic education and high civic consciousness as to understand the importance of living in a multiethnic society. The positive integration among the Malays and Chinese will strengthen a sense of belonging among the Malaysian youths. This study concludes that civic education in this country is important as the foundation for unity and the construction of a dreamed nation-state.